Predicting customer engagement of private hospital: A case study in Malaysia - Adiman, Rohayah; Abd Razak, Noraznira; Muhammad Faisal Wee, Nur Mellisa (Journal of Islamic, Social, Economics and Development, 2025)
This study investigates customer engagement (CE) in private hospitals in Malaysia, focusing on medical and health insurance in the context of the post-COVID-19 environment. Employing the Health Belief Model (HBM) as a theoretical foundation, the research aims to predict CE based on various perceptions. Utilizing variance-based structural equation modeling with Smart PLS 4.0, data was collected from 150 respondents who are private hospital customers. The findings reveal that perceived susceptibility (PS), does not significantly influence CE. However, significant relationships were identified between perceived severity (PI), perceived benefits (PA), and perceived barriers (PB) on CE. These results highlight the importance of emphasizing the severity of health issues and the benefits of medical insurance while addressing barriers to engagement. The implications for hospital management include developing targeted communication strategies that enhance patient understanding and minimize perceived obstacles, ultimately fostering greater CE and loyalty in a competitive healthcare landscape.